Angiotensin Converting Enzyme 2 May Mediate Disease Severity In COVID-19 - Gue, Ying Xuan; Kanji, Rahim; Markides, Vias; Gorog, Diana Adrienne (The American journal of cardiology, 2020)
[...]we propose that measurement of ACE2 level may help identify individuals at risk of severe infection where targeted shielding can be used and could provide a novel therapeutic target. The resultant increased sACE2 may act as a “dummy” receptor, binding the S protein on circulating virus. [...]higher numbers of ACE2 receptors expressed before first binding event may lead to higher sACE2 level and reduced circulating SARS-CoV-2 with “active” S protein sites, reduced numbers of affected host cells, and less systemic impact. [...]conditions that upregulate ACE2 may confer protection, whereas reduced ACE2 expression may result in more severe disease.